Understanding the Parent Experience in Child Custody Decision-Making: How Social Workers Can Help. Issue 2 (April 2019) - Archer-Kuhn, Beth
Parent perspective and experience is largely absent from the research literature in child custody decision-making, making it challenging for social workers to understand the parent experience. Research often focuses on outcome studies regarding children's adjustment and well-being, with little attention to the parent voice. This article addresses this gap using a phenomenological approach. Eighteen participants were recruited from a mid-sized community in Ontario through the mandatory information program (MIP). In-depth interviews and thematic analysis reveal five themes: (a) redefining role, (b) the importance of agency, (c) shared decision-making, (d) the battleground—barriers to shared decision-making, and (e) complexities involved in shared decision-making. These findings illuminate shared parenting challenges, highlighting the need for family supports and services in navigating challenging post-separation realities.